The Resource Curse Revisited and Revised: A Tale of Paradoxes and Red Herrings - Christa N. Brunnschweiler; Erwin H. Bulte (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
We critically evaluate the empirical basis for the so-called resource curse and find that, despite the topic's popularity in economics and political science research, this apparent paradox is a red herring. The most commonly used measure of `resource abundance' can be more usefully interpreted as a proxy for `resource dependence'—endogenous to underlying institutional factors. In multiple estimations that combine resource abundance and dependence, institutional and constitutional variables, we find that (i) resource abundance, constitutions and institutions determine resource dependence, (ii) resource dependence does not affect growth, and (iii) resource abundance positively affects growth and institutional quality.
Keywords: O11; O13; Q0; 330; Natural resource curse; economic growth; growth regressions; political regimes; institutions; constitutions; Natürliche Ressourcen; Wirtschaftswachstum; Politisches System; Dependenztheorie; Schätzung; Welt